Classification Study Period Department of Information Systems at STMIK Bandung Bali using Support Vector Machine (SVM) Method - Zulfachmi, Zulfachmi; Saputra, Aggry; Janardana, I Gusti Ngurah (International Journal of Engineering and Emerging Technology; Vol 3 No 1 (2018): January - June, 2018)
Graduation is the final stage of learning process activities in universities. The undergraduate study period under STMIK Bandung Bali regulation is scheduled in 8 semesters (4 years) or less and a maximum of 14 semesters (7 years). Information Systems is one of the majors in STMIK Bandung Bali. The study period of this department can be influenced by many factors. These factors are the Kumulatid Credit Index (IPK), gender, scholarship, part-time work, Student Activity Unit (UKM). Purpose of this study was to determine the classification of accuracy factors. In this study using SVM (Support Vector Machine) method with accuracy of 99.07%.